تحليل المواد التعليمية في كتاب اللغة العربية لمحمد إلياس مطبعة وزارة الشؤون الدينية على أساس نظرية وليام فرنجيس ماجكي للصف العاشر بالمدرسة الثانوية الإسلامية: Research Article - Sihabuddin (IRecall Journal, 2023)
Teaching materials are textbooks that consist of structured material, making it easier for students to understand the material under the guidance of the teacher in using the achieved language or Arabic both in writing and orally. With teaching materials, students are expected to be able to learn in the classroom and outside the classroom. And the material motivates students to think about everything that is not yet known. As we know that teaching materials vary with different curricula. The objectives of this study are : 1) Knowing the teaching materials in Arabic books by Mohammad Ilyas printed by the Ministry of Religion in grade 10 Madrasah Aliyah Negeri 2 Kediri, 2) Knowing the Analysis of Teaching Materials in Arabic books by Mohammad Ilyas printed by the Ministry of Religion with William Francis Theory Mackey in grade 10 Madrasah Aliyah. The result of this study is that the selection of material is not in accordance with the theory of William Francis Mackey because there are no teacher guidelines and core competencies. On the gradation of material according to the theory of William Francis Mackey on grouping and sorting, on the grouping of material according to students' daily activities and the sorting of material is appropriate. The delivery of the material is in accordance with William Francis Mackey's theory because it includes differential procedures, authentic procedures, pictoral procedures, and contextual procedures. And the repetition of material is in accordance with William Francis Mackey theory because there is already repetition (sharpening of material) in listening skills, speaking skills, reading skills, writing skills, vocabulary and arabic grammar.